Local Wisdom of Nias Island Community Facing the Earthquake and Tsunami - Anatona, Anatona; Elvira, Maiza; Nur, Mhd.; Zalukhu, Riski Syukri (Environment-Behaviour Proceedings Journal, 2023)
This article describes the forms of local wisdom of the people of Nias Island in dealing with the natural disasters of the earthquake and tsunami. Nias Island, which is located on the west coast of Sumatra, is one of the islands included in the Eurasian plate fault in the Indian Ocean, which has periodically shaken due to earthquake shocks, which are sometimes accompanied by tsunami waves. To anticipate the impact of the earthquake and tsunami, the Nias community has several of local wisdom by building traditional houses to live in hilly areas that are located far from the seaside.